Structural and electronic response of overexpanded superconducting fullerides close to the Mott insulator boundary - Menelaou, Melita; Takabayashi, Yasuhiro; Okur, H. Esma; Zadik, Ruth H.; Prassides, Kosmas (My University, 2018)
The ternary fulleride, Rb0.25Cs2.75C60, is the most expanded member of the family of face-centered cubic (fcc) structured superconducting fullerides ever accessed with superconductivity surviving at ambient pressure closest to the Mott insulator boundary. Here, we study the evolution of its structural and electronic properties with temperature. At ambient temperature, Rb0.25Cs2.75C60 lies in the Mott-Jahn-Teller (MJT) insulating part of the phase diagram. High-resolution synchrotron X-ray diffraction shows that its structure remains strictly cubic at all temperatures, but the transition to the metallic state at ∼ 50 K - evident in the evolution of the magnetic susceptibility with temperature - is accompanied by a lattice collapse, ΔV/V0 of - 0.5%. Bulk superconductivity then emerges on further cooling with a Tc of 25.9 K. The results permit the extension of the electronic phase diagram of A3C60 fullerides as close as possible to the metal-insulator (M-I) crossover.
Keywords: electronic phase diagram; insulator-metal transition; Mott insulator; strong correlations; Superconductivity